Complexités des prix littéraires et littérature française ou en français - Marie-Manuelle da Silva; Eduarda Keating (Carnets)
In the French « literary nation », prices proliferate in what Sylvie Ducas (2006) designates as an economy of prestige based, on the one hand, on mythologies associated with writers and, on the other, on ways of defining « literary value ». This paper examines some of the interactions between the literary phenomenon represented by the Nobel Prize and the French literary field, and analyzes the transformation of the classical idea of the writer inherited from the Ancien Régime through the rhetoric and models supported by the Nobel Prize for Literature since the award of the Prize to Sartre in 1964.